Pengelompokan Dan Perbandingan Pembangunan Sosial Provinsi Di Indonesia - Banjar Nahor, Anne Indiarti (Indonesian Journal of Applied Statistics, 2022)
Social development still not become priority in policy formulation in Indonesia. The reality of development without social aspects will not be able to be enjoyed evenly by the community. This study examines social development in Indonesia by grouping social development issues and comparing social development achievements in 2016-2017 to find out which areas should be a priority. Eleven social development indicators was used to present social development in Indonesia. Biplot analysis as an initial indication of regional grouping based on social development indicators, and cluster analysis to facilitate interpretation of grouping results. The percentage of diversity data that can be worked on by biplot analysis are 65 percent for 2016 and 61,3 percent for 2017. The results of biplot analysis produce character variables from each province based on the quadrant. It can be seen that in quadrant II the members of the Province of Bangka Belitung Islands, East Java, Central Java, North Sulawesi, West Nusa Tenggara, Central Sulawesi are characterized by high scores on health dimension variables, literacy rates and the percentage of households with adequate access. Based on the cluster analysis produce the group of provinces according to three levels of social development namely low, medium, high. Papua Province is the only province that does not change and still exists at a low level of social development.Keywords: social development, biplot analysis, cluster analysis